Targeting Inflammation in Rotator Cuff Tendon Degeneration and Repair - Abraham, Adam C. (Tech Shoulder Elb Surg, 2017)
Rotator cuff degeneration is a common affliction that results in pain and disability. Tendinopathy was historically classified with or without the involvement of the immune system. However, technological advancements in screening have shown that the immune system is both present and active in all forms of tendinopathy. During injury and healing, the coordinated effort of numerous immune cell populations work with the resident stromal cells to break down damaged tissues and stimulate remodeling. These cells deploy a wide array of tools, including phagocytosis, enzyme secretion, and chemotactic gradients to direct these processes. Yet, there remains a knowledge gap in our understanding of the sequence of critical events and regulatory factors that mediate this is process in injury and healing. Furthermore, current treatments do not specifically target inflammation at the molecular level. Typical regimens include non-steroidal anti-inflammatory drugs or corticosteroids; however, researchers have found irrevocable functional deficits following treatment, and have disputed their long-term efficacy. Therefore, developing therapeutics that specifically consider the nuances of the immune system are necessary to improve patient outcomes.